Penerapan Good Electrical Practices Berdasarkan Evaluasi Sistem Kelistrikan Tower BTS di Kabupaten Madiun - Budi Triyono; Dimas Nur Prakoso; Raden Jasa Kusumo Haryo; Hanifah Nur Kumala Ningrum; Budi Artono; Ferdiansyah Prasetya Utama (Jurnal Pengabdian Masyarakat, 2025)
This Community Service Program aims to improve the reliability and safety of electrical systems at partner Base Transceiver Station (BTS) sites through the adoption of Good Electrical Practices (GEP). The activities comprise four core components: (1) a light GEP-based audit to identify nonconformities in overcurrent protection, grounding systems, panel management, cabling, and safety aspects; (2) practical training for technicians on visual inspection, electrical safety, and basic measurements; (3) on-the-job mentoring to implement prioritized fixes; and (4) standardization of working tools (SOPs, checklists, and logbooks) to ensure sustainability. The results show tangible improvements in aligning protection ratings/curves (MCB/MCCB), enhancing grounding and lightning protection quality, improving panel tidiness and circuit labeling, and strengthening maintenance documentation discipline. Operational impacts are reflected in a trend toward reduced fault frequency and downtime, improved panel thermal conditions during peak hours, and better feeder voltage drop. The participatory, phased intervention model focused on quick wins proved effective, resource-aligned for partners, and readily replicable at other sites. The program recommends periodic monitoring based on SOPs and peer audit to maintain consistency of best practices.